PCA-based metagenomics reveals functional and taxonomic diversity in Kedu chicken gut microbiota - NURULIARIZKI SHINTA PANDUPUSPITASARI; SUGIHARTO SUGIHARTO; IKANIA AGUSETYANINGSIH; DELA AYU LESTARI; FAHEEM AHMED KHAN; ASEP SETIAJI; MUHAMMAD ASIF RAZA (Society for Indonesian Biodiversity, 2025)
Abstract. Pandupuspitasari NS, Sugiharto S, Agusetyaningsih I, Lestari DA, Khan FA, Setiaji A, Raza MA. 2025. PCA-based metagenomics reveals functional and taxonomic diversity in Kedu chicken gut microbiota. Biodiversitas 26: 4035-4041. The Gastrointestinal Tract (GIT) microbiota plays a central role in poultry health, productivity, and resilience, influencing digestion, nutrient absorption, immune development, and disease resistance. This study provides the first multi-database Principal Component Analysis (PCA)-based metagenomic characterization of the gut microbiota in Kedu chickens (Gallus gallus (Linnaeus, 1758)), an indigenous Indonesian breed. Digesta from five GIT segments (crop, gizzard, jejunum, colon, and cecum) of 21 traditionally reared Kedu chickens were sequenced on the Illumina NovaSeq X Plus platform, yielding 1,523,876 unigenes. Functional annotation against Non-Redundant Protein Database (NR), Clusters of Orthologous Groups (COG), Kyoto Encyclopedia of Genes and Genomes (KEGG), Carbohydrate-Active enZYmes Database (CAZy), Antibiotic Resistance Genes Database (ARDB), Comprehensive Antibiotic Resistance Database (CARD), and Virulence Factor Database (VFDB) revealed enrichment of genes involved in metabolism (38.2%), cellular processes (15.7%), environmental information processing (12.6%), and genetic information processing (11.0%). PCA separated GIT segments by functional specialization: The jejunum clustered distinctly (PC1 variance = 26.48% for NR, 30.04% for COG, 67.16% for KEGG) due to nutrient absorption-related functions, while the cecum exhibited the highest diversity and carbohydrate-active enzyme profiles (PC1 = 24.98% for CAZy). ARDB/CARD analysis showed that distal GIT segments (colon, cecum) contained higher densities of antimicrobial resistance genes, and VFDB revealed elevated virulence factor abundance in ileum and cecum. These findings highlight segment-specific microbiota roles, supporting the development of targeted probiotics and feed strategies, and contribute to conserving the functional biodiversity of Kedu chickens in sustainable production systems.